Female Sexual Dysfunction Among Married Women from the Nile Delta of Egypt. Issue 2 (3rd April 2019) - Mustafa, Amany Ibrahim; El Esawy, Fatma Mohamed; Fawzy, Iman
Abstract: Objectives : Sexuality is an essential part of every woman's life. Information about female sexuality is scant in Egypt and many other Islamic countries due to cultural barriers. Thus, epidemiological investigations regarding the prevalence and risk factors of female sexual dysfunction (FSD) are limited. We aimed at being the first to assess the prevalence and possible risk factors of FSD among a sample of married Egyptian women from the Nile Delta region in Egypt. Methods : Participants of this cross-sectional descriptive hospital-based study were 5, 600 married women 18–59 years' old attending the Dermatology and Andrology and Family planning outpatient clinic of Benha University Hospitals and/or their relatives. Female Genital Mutilation was assessed using the Female Sexual Function Index (FSFI) questionnaire. Data were analyzed using appropriate methods used for statistical purposes. Results : On evaluating sexual function, desire and orgasm were the most affected domains. Considering the total FSFI score of ≤26.55 was the cutoff value for the diagnosis of FSD, 45.6% of studied participants were suffering from sexual dysfunction versus 54.6 who had normal sexual functioning ( p = 0.003). Logistic regression analysis was conducted for prediction of factors associated with sexual dysfunction using age, duration of marriage, education level, residence, and female genital mutilation as covariates. Older age, longer duration of the marriage, lower educational level, female genital mutilation, older male partner age, male erection, and ejaculation problems were associated with sexual dysfunction in univariable and multivariable analyses, respectively. Conclusions : The current study is one of the first attempts to evaluate the prevalence of FSD among married women from the Nile Delta of Egypt. It was revealed that FSD was highly prevalent among studied participants. Combined female participant and male partner factors were significantly associated with the high prevalence of this problem.